Effect of seawater immersion on the explosive blast response of a carbon fibre-polymer laminate. (June 2018) - Gargano, A.; Pingkarawat, K.; Pickerd, V.; Delaney, T.; Das, R.; Mouritz, A.P.
Abstract: Explosions are an ever-present risk to laminates used in naval ships, submarines and offshore oil/gas platforms that are immersed in seawater. This study determines whether the absorption of water by a carbon fibre laminate changes its deformation response and damage resistance when impulsive loaded by an explosive blast. The stiffness and strength properties of the laminate were reduced with increasing immersion time in seawater up to and beyond the point of saturation. Explosive blast tests of increasing shock wave impulse were performed on the laminate before immersion and when in the saturated and beyond saturated conditions. Softening and weakening of the laminate caused by absorbed water reduced the resistance against deformation and damage when subjected to an explosive blast. The amount of blast-induced damage to the laminate increased with the immersion time in seawater due to plasticisation of the polymer matrix and weakening of the fibre–matrix interphase region.